Tree Ring and Climate change in Langtang National Park, Central Nepal - Chhetri, P.K.; Thapa, S. (Our Nature, 2011)
In present study 120 tree cores from 60 trees of Abies spectabilis from two different sites Chandanbari and Cholangpati area of Langtang National Park were collected. Analysis of increment cores showed that trees in those stands were 100-300 years old. Trees of Chandanbari site were found to be older than Cholangpati. Mean tree ring width of Chandanbari was 2.34 mm and that of Cholangpati site 1.70 mm. Growth rate was higher (2.34 mm/yr) at the Chandanbari than that of Cholangpati (1.70 mm/yr). Series intercorrelation and mean sensitivity were 0.457 and 0.223 for Chandanbari and 0.499 and 0.203 for Cholangpati, respectively. The high mean sensitivity value indicated that high inter-annual variability was present in the ring widths and that the chronology was sensitive to yearly environmental changes; ring width was negatively correlated with minimum monthly temperature and positively correlated with total monthly precipitation. DOI: 10.3126/on.v8i1.4321